The Urgency of The Selarian Statement In Proof of The Eligibility of Marriage Dispensation Cases In The Bima Class 1A Religious Court - Zulkarnain, Feri; Jainuddin, Jainuddin; Putra, Muh. Yunan (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This research explores the urgency and legal relevance of the Surat Pernyataan Selarian (Elopement Statement Letter) in proving the feasibility of marriage dispensation applications at the Bima Class 1A Religious Court. Marriage dispensation, which allows underage couples to legally marry under special conditions, often involves cultural elements such as elopement, especially in traditional communities like Bima. The study aims to assess how this letter functions as supporting evidence, its legal standing, and the extent to which it influences judicial decisions. Using an empirical qualitative method, the research was conducted through field observations, in-depth interviews with judges and court staff, and document analysis of dispensation case files. The findings reveal that although the elopement statement letter is not legally mandated, it is commonly submitted to demonstrate the seriousness of the couple’s relationship and to gain social legitimacy. Judges often take the letter into consideration as it reflects cultural values and community support, even though it lacks formal legal weight. The study also identifies challenges in the use of such letters, including lack of standardization, risk of fabrication, and inconsistency in judicial interpretations. The practice reveals a tension between formal legal standards and traditional customs, raising concerns about the protection of minors and the uniformity of legal application. In conclusion, while the elopement statement letter holds cultural significance and practical influence in local court procedures, its legal implications require careful regulation. The research recommends establishing clearer guidelines and integrating formal support mechanisms to ensure that cultural practices do not undermine the legal protections intended for children.   [Penelitian ini mengeksplorasi urgensi dan relevansi yuridis dari Surat Pernyataan Selarian dalam pembuktian kelayakan permohonan dispensasi nikah di Pengadilan Agama Bima Kelas 1A. Dispensasi nikah, yang memungkinkan pasangan di bawah umur untuk menikah secara sah dalam kondisi tertentu, sering kali melibatkan unsur budaya seperti praktik selarian, khususnya di masyarakat tradisional seperti Bima. Penelitian ini bertujuan untuk menilai bagaimana surat tersebut berfungsi sebagai alat bukti pendukung, kedudukan hukumnya, serta sejauh mana pengaruhnya terhadap pertimbangan hakim dalam pengambilan putusan. Dengan menggunakan metode kualitatif empiris, penelitian ini dilakukan melalui observasi lapangan, wawancara mendalam dengan hakim dan staf pengadilan, serta analisis dokumen berkas perkara dispensasi nikah. Temuan penelitian menunjukkan bahwa meskipun Surat Pernyataan Selarian tidak diwajibkan secara hukum, surat ini umumnya dilampirkan untuk menunjukkan keseriusan hubungan pasangan serta memperoleh legitimasi sosial. Hakim sering mempertimbangkan surat tersebut karena mencerminkan nilai-nilai budaya dan dukungan masyarakat, meskipun surat itu tidak memiliki kekuatan hukum formal. Penelitian ini juga mengidentifikasi berbagai tantangan dalam penggunaan surat tersebut, termasuk tidak adanya standar baku, potensi pemalsuan, dan ketidakkonsistenan dalam interpretasi yudisial. Praktik ini memperlihatkan adanya ketegangan antara standar hukum formal dengan adat istiadat lokal, yang menimbulkan kekhawatiran terhadap perlindungan anak dan keseragaman penerapan hukum. Sebagai kesimpulan, meskipun Surat Pernyataan Selarian memiliki makna kultural dan pengaruh praktis dalam prosedur peradilan lokal, implikasi hukumnya memerlukan pengaturan yang cermat. Penelitian ini merekomendasikan perlunya pedoman yang lebih jelas serta integrasi mekanisme pendukung formal guna memastikan bahwa praktik budaya tidak melemahkan perlindungan hukum yang ditujukan bagi anak-anak.]